Analysis Of Company Financial Performance With Du Pont System (Study Of Hotel Companies Listed On The Indonesia Stock Exchange In The Period 2018-2022) - Nyoman Reditiasari; Zuhrotul Isnaini (Citakonsultindo, 2024)
This study uses the Du Pont System to analyze the financial performance of hotel companies listed on the Indonesia Stock Exchange (IDX) during 2018-2022. The variables used include Net Profit Margin, Total Asset Turn Over, and Return On Investment. The data used in this study are secondary. The purposive sampling method was used. The results of this study indicate that the financial performance of hotel companies listed on the Indonesia Stock Exchange in 2018-2022 needs to be better because it decreased during the COVID-19 pandemic. This causes the Net Profit Margin and Total Asset Turn Over values to decline, affecting the Return On Investment value.